PENGARUH APLIKASI PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELEDRI (Apium graveolens L.) PADA MEDIA GAMBUT - Dalimunthe, Badrul Ainy (JURNAL AGROPLASMA, 2019)
Celery (Apium graveolens L.) is a vegetable plant that has long been known in Indonesia. Celery plants have many benefits. Celery plants come from Europe, especially in the Mediterranean region around the Mediterranean Sea. This plant spreads to the Plains of China, India, Central Asia, Ethiopia, South and Central Mexico and the United States the influence of NPK fertilizer on the growth and yield of celery plants on peat media. This research was conducted on Kenanga Street, Teluk Panji IV, Kampung Rakyat Subdistrict, Labuhan Batu Selatan Regency, at an altitude of ± 23 m above sea level. This activity will be carried out from February 2019 to May 2019. The design used is a randomized single factor group design that is with NPK fertilizer dosage: Treatment P0: (control), P1: (5 g / plant) P2: (10 g / plant ). The parameters observed were plant height (cm), number of leaves (strands), number of tillers, harvest weight (g). From the results of data analysis it was found that the effect of NPK Phonska fertilizer (15; 15; 15) can increase the growth of celery plant. The highest plant height (11.93 cm) Number of leaves (6.5 strands) Number of tillers (8.66) Weight of harvest (17.5 g). NPK Phonska fertilizer (15; 15; 15) is recommended with a dose of P2: (10 g / plant). Keywords : Celery (Apium graveolens L.), NPK, Peat Soil